Extracción de aceite esencial de Ruda (ruta graveolens) mediante la metodología de arrastre de vapor. - Fernández Romero, Lizbeth Tatiana (2022)
In the present research study, ruda essential oil (Ruta graveolens) was extracted by using the steam destillation method using “XIAOJIAN” (Lanphan Ltd., China) equipment in a laboratory of the Faculty of Agricultural Sciences and Natural Resources (CAREN) at Technical University of Cotopaxi. The humidity of the vegetable matter was determined with a result of 71.22%, to optimize the extraction process it was used of the Design Expert 8.0.6. software in which 17 experimental runs were established and the control factors were the relationship between time (60, 105, 150 min) and mass/dissolvent (1.1:3; 2.1:4; 3.1:5 kg/l), through the optimization of the process the following optimal conditions were identified mass/dissolvent 3. (1:5 kg/l) and 150 minutes, with the processing of the data obtained a predicted yield of 0.14% and an experimental yield of 0.13% were determined. It should be highlight that these values have a difference of 0,001% so there is a similarity between both. In addition, composition chemical was analyzed out through gas chromatography coupled to a mass spectrometer detector in the Agilent Techologies 5975C inert XL MSD with Triple – Axis Detector where various organic compounds of Ruda essential oil were found and ketones predominated, 2- Undecanone (46.74%) and 2-Nonanone (29.14%) and to a lesser extent Limonene (0.06%), the antioxidant capacity of 37.67 μmol 46,46 μmol 〖Fe〗^(2+)/g in the FRAP assay and 46.46 µmol TE/g in the ABTS assay, antimicrobial efficacy was detected on the bacterias at 3% on Listeria monocytogenes, Bacillus cereus, and Pseudomonas aeruginosa and with 5% Salmonella entérica, Staphylococcus aureus and Escherichia coli